ALDH2 mediates the effects of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on improving cardiac remodeling - Han Liu; Bingchen Jiang; Rui Hua; Xuehao Liu; Bao Qiao; Xiangxin Zhang; Xilong Liu; Wenjun Wang; Qiuhuan Yuan; Bailu Wang; Shujian Wei; Yuguo Chen (Cardiovascular Diabetology)
Abstract Background Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are now recommended for patients with heart failure, but the mechanisms that underlie the protective role of SGLT2i in cardiac remodeling remain unclear. Aldehyde dehydrogenase 2 (ALDH2) effectively prevents cardiac remodeling. Here, the key role of ALDH2 in the efficacy of SGLT2i on cardiac remodeling was studied. Methods Analysis of multiple transcriptomic datasets and two-sample Mendelian randomization were performed to find out the differentially expressed genes between pathological cardiac hypertrophy models (patients) and controls. A pathological cardiac hypertrophy mouse model was established via transverse aortic constriction (TAC) or isoproterenol (ISO). Cardiomyocyte-specific ALDH2 knockout mice (ALDH2CMKO) and littermate control mice (ALDH2flox/flox) were generated to determine the critical role of ALDH2 in the preventive effects of dapagliflozin (DAPA) on cardiac remodeling. RNA sequencing, gene knockdown or overexpression, bisulfite sequencing PCR, and luciferase reporter assays were performed to explore the underlying molecular mechanisms involved. Results Only ALDH2 was differentially expressed when the differentially expressed genes obtained via Mendelian analysis and the differentially expressed genes obtained from the multiple transcriptome datasets were combined. Mendelian analysis revealed that ALDH2 was negatively related to the severity of myocardial hypertrophy in patients. DAPA alleviated cardiac remodeling in mouse hearts subjected to TAC or ISO. ALDH2 expression was reduced, whereas ALDH2 expression was restored by DAPA in hypertrophic hearts. Cardiomyocyte specific ALDH2 knockout abolished the protective role of DAPA in preventing cardiac remodeling. ALDH2 expression and activity were increased in DAPA-treated neonatal rat primary cardiomyocytes (NRCMs), H9C2 cells and AC16 cells. Moreover, DAPA upregulated ALDH2 in peripheral blood mononuclear cells (PBMCs) from patients with type 2 diabetes. Sodium/proton exchanger 1 (NHE1) inhibition contributed to the regulation of ALDH2 by DAPA. DAPA suppressed the production of reactive oxygen species (ROS), downregulated DNA methyltransferase 1 (DNMT1) and subsequently reduced the ALDH2 promoter methylation level. Further studies revealed that DAPA enhanced the binding of nuclear transcription factor Y, subunit A (NFYA) to the promoter region of ALDH2, which was due to the decreased promoter methylation level of ALDH2. Conclusions The upregulation of ALDH2 plays a critical role in the protection of DAPA against cardiac remodeling. DAPA enhances the binding of NFYA to the ALDH2 promoter by reducing the ALDH2 promoter methylation level through NHE1/ROS/DNMT1 pathway. Graphical abstract